Knowledge and Awareness Regarding Denture Staining Amount Complete Denture Wearers: A Descriptive Questionnaire Survey - Rathi, A; Jha, RK; Bhochhibhoya, A; Guragain, M (Journal of Nepalese Prosthodontic Society, 2022)
Introduction: Improper denture hygiene leads to denture staining as well as various lesions of the oral mucosa associated with wearing of removable dentures. The aim of the study is to evaluate the knowledge and awareness regarding denture staining amount complete denture wearers visiting Dental Department, Nobel Medical College and Teaching Hospital. Methods: A descriptive cross‑sectional study was conducted among complete denture wearers visiting Dental Department of Nobel Medical College and Teaching Hospital. A survey was conducted through a printed standard questionnaire with 15 questions delivered to the patients. Data were collected and coded, the statistical analysis was done using SPSS statistical software package. Descriptive statistics were used for data analysis. Results: The study showed that about 38 % of the patients were denture wearers for 6 months to 1 year. About 97% of patients consume coffee or tea regularly. About 65% of the patients consumed aerated beverages. 52% of the patients reported alcohol consumption habits. Tobacco chewing habit was reported by 7% of the patients. 17% of the patients reported cigarette smoking habit. Almost 92.9%% of the patients cleaned their dentures using some or the other method. 64% of the patients claimed to be aware of some or the other denture cleaning techniques. About 20.2% of the patients complained of halitosis, 11% of the patients complained of oral ulcers, and approximately 68.8% of the patients suffered from oral infections. Conclusion: The knowledge and awareness regarding the cleaning and staining of dentures was not adequate among study participants. Patients have habit of consuming tea, coffee, aerated drinks and alcohol which could lead to staining of the acrylic dentures. Therefore, care and hygiene of dental prosthesis including removable dentures is a life-long exercise.